A temperature-sensitive single-layer hydrogel with controllable transparency, preparation method and assembled double-layer hydrogel

By introducing specific monomers and crosslinking agents into the hydrogel, a temperature-sensitive monolayer hydrogel with controllable transparency is prepared, and a double-layer hydrogel with high response rate is formed through double-layer assembly, which solves the problems of slow response rate and lack of obvious transparency changes in existing hydrogels, and achieves efficient deformation driving force and excellent mechanical properties.

CN114891241BActive Publication Date: 2025-03-14QUZHOU RES INST OF ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210410021.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-19
Publication Date
2025-03-14
Estimated Expiration
2042-04-19

AI Technical Summary

Technical Problem

The existing double-layer hydrogel based on poly(acrylamide-acrylic acid) has the problem of slow response rate and lack of obvious transparency changes, and it is difficult to improve its response rate while ensuring the transparency conversion efficiency.

Method used

Through simple radical polymerization, chemical crosslinking agents and specific monomers, such as acryloyloxyethyltrimethylammonium chloride and fatty alcohol polyoxyethylene ether-9, a temperature-sensitive monolayer hydrogel with controllable transparency is prepared and used for double-layer assembly to form a double-layer hydrogel with high bond strength and fast reversible deformation.

Benefits of technology

It realizes rapid reversible transparency changes of single-layer hydrogels and high response rate of double-layer hydrogels, excellent mechanical performance, and is suitable for intelligent drivers, soft robots and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114891241B_ABST
    Figure CN114891241B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of intelligent hydrogels, and discloses a method for preparing a temperature-sensitive single-layer hydrogel with controllable transparency, comprising the following steps: (1) dissolving acrylamide, acrylic acid, and cyclodextrin monomers in water, adding acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9, and a crosslinking agent and mixing them thoroughly; then adding an initiator and a catalyst to obtain a hydrogel prepolymer; (2) injecting the hydrogel prepolymer in step (1) into a mold to react and obtain a single-layer hydrogel. The single-layer hydrogel has excellent mechanical properties and a rapid transparency change capability. The present invention also uses the single-layer hydrogel for double-layer assembly through the host-guest interaction between cyclodextrin and isopropyl, and prepares a double-layer hydrogel with high double-layer bonding strength and capable of realizing rapid and reversible anisotropic deformation. The single-layer hydrogel and the double-layer hydrogel have broad application prospects in the fields of intelligent actuators, soft robots, biomedical devices, or artificial muscles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of smart hydrogels, and in particular relates to a temperature-sensitive single-layer hydrogel with controllable transparency, a preparation method and a double-layer hydrogel obtained by assembly. Background Art

[0002] Smart hydrogel is a new type of polymer material with a three-dimensional network structure, which has strong water absorption and water retention. As a special soft material, hydrogel has special properties such as deformation, swelling, stimulus response, and shock absorption, and is widely used in various fields. Among them, stimulus-responsive hydrogels will produce a variety of functional reactions and changes in morphology and volume when exposed to the external environment (temperature, light, pH, electric field, magnetic field, etc.). These stimulus-responsive hydrogels have broad application prospects in the fields of smart actuators, soft robots, biomedical devices, artificial muscles, etc.

[0003] Hydrogels with temperature responsive properties will undergo a certain degree of volume phase transition, achieving complex deformation of the hydrogel (such as bending, twisting, folding, etc.), which are generally caused by anisotropic swelling or contraction of different magnitudes in different directions. Double-layer hydrogel is an important way to achieve anisotropic deformation of hydrogels. Ma et al. prepared a double-layer hydrogel based on temperature-responsive graphene oxide-poly (N-isopropylacrylamide) hydrogel (Ma et al., Bioinspired anisotropic hydrogel actuators with on-off switchable and colortunable fluorescence behaviors. Adv. Funct. Mater. 2018, 28 (7): 1704568), but its bending rate is slow, and an additional "polymer glue" needs to be designed to increase the double-layer connection strength, which is difficult to synthesize.

[0004] Temperature-responsive hydrogels mainly include low-temperature swelling type and high-temperature swelling type. Low-temperature swelling type hydrogels have a low critical solution temperature and are usually based on poly (N-isopropylacrylamide), and their volume phase transition temperature is around 32-33 ° C. Correspondingly, high-temperature swelling type hydrogels have a high critical solution temperature, and many current works focus on hydrogel systems composed of acrylamide and acrylic acid. Hua et al. synthesized a double-layer hydrogel actuator based on polyacrylamide and polyacrylic acid, including a layer of interpenetrating network of poly (acrylamide-acrylic acid) and another layer of polyacrylamide network to achieve anisotropic deformation (Hua et al., Mimosa inspired bilayer hydrogel actuator functioning in multi-environments. J. Mater. Chem. C 2018, 6 (6): 1320-1327). However, in this work, the response speed of the hydrogel is slow, which has certain limitations in application, and the changes in the transparency of the hydrogel have not been explored in detail.

[0005] The hydrogel prepared by random copolymerization of acrylamide and acrylic acid exhibits slow swelling / de-swelling behavior, and this hydrogel is opaque at low temperatures. As the temperature rises, the hydrogel gradually becomes transparent, and the whole process is reversible. The change in transmittance can quantitatively explain the change in its macroscopic transparency. At present, the double-layer hydrogel system based on poly(acrylamide-acrylic acid) has problems such as slow response rate and unclear transparency change. Therefore, it is an important research direction to improve the response rate while ensuring the transparency conversion efficiency of the hydrogel. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides a simple, feasible, and easy-to-control method for preparing a temperature-sensitive single-layer hydrogel with controllable transparency, and the prepared single-layer hydrogel is used for double-layer assembly to prepare a double-layer hydrogel with high double-layer bonding strength and rapid and reversible anisotropic deformation. The single-layer hydrogel and the double-layer hydrogel have broad application prospects in the fields of intelligent actuators, soft robots, biomedical devices, or artificial muscles.

[0007] The specific technical solutions adopted are as follows:

[0008] A method for preparing a temperature-sensitive single-layer hydrogel with controllable transparency comprises the following steps:

[0009] (1) dissolving acrylamide, acrylic acid and cyclodextrin monomers in water, adding acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9 and a crosslinking agent and mixing thoroughly; then adding an initiator and a catalyst to obtain a hydrogel prepolymer solution;

[0010] (2) Injecting the hydrogel prepolymer solution in step (1) into a mold to react and obtain a single-layer hydrogel.

[0011] The invention adopts simple free radical polymerization and adds a chemical crosslinking agent to copolymerize acrylamide, acrylic acid and acryloyloxyethyl trimethyl ammonium chloride to obtain a single-layer hydrogel. The interior of the single-layer hydrogel forms a three-dimensional network through physical-chemical crosslinking, and the physical crosslinking effect includes hydrogen bonding and electrostatic interaction.

[0012] The amide group of acrylamide and the carboxyl group of acrylic acid show strong intermolecular hydrogen bonds (polymer-polymer hydrogen bonds), water molecules are excluded from the hydrogel, and the hydrogel shows an opaque state. When the temperature rises above the high critical solution temperature, the intermolecular hydrogen bonds between the amide group and the carboxyl group become extremely unstable and easily broken, while stable hydrogen bonds (polymer-water hydrogen bonds) are formed between the polymer molecules and water. Therefore, the hydrogel absorbs water and swells, and the transparency increases, and the overall state changes from an opaque state to a transparent state. The present invention further introduces the cationic monomer acryloyloxyethyltrimethylammonium chloride, whose cationic group can form anionic and cationic electrostatic interactions with the carboxyl group of acrylic acid, which has a positive effect on the temperature sensitivity of the hydrogel. After the non-ionic surfactant fatty alcohol polyoxyethylene ether-9 is introduced into the hydrogel, its hydrophobic groups are tightly combined together to minimize the contact area with water and form micelles. These micelles are fixed in the hydrogel network by forming hydrogen bonds with acryloyloxyethyltrimethylammonium chloride, acrylic acid and acrylamide. The formation of micelles reduces the resistance of water molecules entering and exiting the internal network of the hydrogel, and can obtain a wider range of swelling rate changes without affecting the transparency changes of the hydrogel at 25-50°C.

[0013] Preferably, the cyclodextrin monomers include β-cyclodextrin monomers and α-cyclodextrin monomers.

[0014] Preferably, in step (1), the ratio of acrylamide, acrylic acid, and acryloyloxyethyl trimethyl ammonium chloride is 1 mg: 1 μL: 0.3-0.4 mg. There is hydrogen bonding interaction between acrylamide and acrylic acid; electrostatic interaction can be formed between acryloyloxyethyl trimethyl ammonium chloride and acrylic acid, thereby enhancing the high critical solution temperature characteristics; under the above preferred ratio range, the hydrogen bonding interaction between acrylamide and acrylic acid is the strongest, and a single-layer temperature-sensitive hydrogel with good mechanical properties and obvious volume phase transition with temperature changes can be prepared.

[0015] When the content of acryloyloxyethyltrimethylammonium chloride is too high, it will lead to a large difference in internal and external osmotic pressure in the initial formation stage of the hydrogel, and water molecules will continuously enter the hydrogel, causing the mechanical properties of the hydrogel to deteriorate and even lose its shape-retaining ability.

[0016] Preferably, in step (1), the crosslinking agent comprises N,N-methylenebisacrylamide, and the added molar amount is 1-2% of the total molar mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride; the crosslinking agent can provide a chemical crosslinking network for the hydrogel, determine the crosslinking density of the hydrogel, and thus affect its mechanical properties; the single-layer temperature-sensitive hydrogel also has hydrogen bonds and electrostatic interactions as physical crosslinks. If the amount of crosslinking agent added is too much and the crosslinking density is too high, the polymer chains will be tightly entangled, resulting in a decrease in the mechanical properties of the hydrogel and easy breakage.

[0017] Preferably, the amount of fatty alcohol polyoxyethylene ether-9 added is 60-80wt% of acrylamide. The addition of fatty alcohol polyoxyethylene ether-9 is beneficial to improving the response rate and enhancing the transparency change trend, but when the content is too high, there is not enough hydrogen bonding to combine it in the hydrogel network, and fatty alcohol polyoxyethylene ether-9 will precipitate from the hydrogel during immersion.

[0018] In step (1), the initiator includes potassium persulfate or ammonium persulfate, and the amount of the initiator added is 1-3wt% of the total mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride; the catalyst includes N,N,N',N'-tetramethylethylenediamine, and the amount of the catalyst is 3-8μL / mL based on the total volume of the hydrogel prepolymer solution.

[0019] In step (2), the process of injecting into the mold needs to be completed within 5 minutes, the reaction temperature is ≥50°C, and the reaction time is ≥16 hours.

[0020] Preferably, in step (2), the process of injecting into the mold should be completed within 1 minute. After adding the initiator and the catalyst, the free radical polymerization process of the hydrogel is very rapid and can start polymerization within a few minutes. The operation within 1 minute can ensure that the solution is injected into the mold to prevent clogging of the syringe. The temperature of sudden transparency change between acrylamide and acrylic acid is about 40°C, and the cloud point of fatty alcohol polyoxyethylene ether-9 is 71-85°C. In order to prevent sudden transparency change and precipitation of fatty alcohol polyoxyethylene ether-9, ensure sufficient polymerization of the hydrogel monomer, and reduce the loss of reactants, the reaction temperature is preferably 50-70°C, and the reaction time is preferably ≥24h.

[0021] The present invention also provides a single-layer hydrogel prepared by the preparation method of the temperature-sensitive single-layer hydrogel with controllable transparency. The single-layer hydrogel has excellent mechanical properties, can achieve rapid and reversible transparency changes, and has a fast response speed.

[0022] A method for preparing a double-layer hydrogel comprises the following steps:

[0023] (I) dissolving acrylamide, acrylic acid and cyclodextrin monomers in water, adding acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9 and a crosslinking agent and mixing thoroughly; then adding an initiator and a catalyst to obtain a hydrogel prepolymer solution;

[0024] (II) dissolving N-isopropylacrylamide and a crosslinking agent in deionized water and mixing them evenly, adding an initiator and a catalyst to obtain a mixed solution, and injecting the mixed solution into a mold to react and obtain an assembly layer hydrogel;

[0025] (III) injecting the hydrogel prepolymer solution of step (I) into the mold of step (II) to obtain the double-layer hydrogel.

[0026] The present invention utilizes the host-guest interaction between cyclodextrin and N-isopropylacrylamide isopropyl to perform double-layer assembly of the hydrogel prepolymer liquid system and poly N-isopropylacrylamide hydrogel to prepare a double-layer hydrogel. The hydrogel prepolymer liquid forms a three-dimensional network single-layer hydrogel through physical-chemical crosslinking. The single-layer hydrogel has a high critical solution temperature and is characterized by low-temperature water loss shrinkage and high-temperature water absorption expansion. The assembled layer hydrogel has a low critical solution temperature and is characterized by high-temperature hydrophobic shrinkage and low-temperature hydrophilic swelling. Two temperature-sensitive systems with opposite trends are integrated into the same double-layer hydrogel through the host-guest interaction. The double-layer bonding strength is high. At the same time, the response difference of different hydrogels to temperature is utilized to achieve rapid and reversible anisotropic deformation.

[0027] The preparation method of the hydrogel prepolymer solution in step (I) is the same as that of the hydrogel prepolymer solution in step (1).

[0028] Preferably, the cyclodextrin monomers include β-cyclodextrin monomers and α-cyclodextrin monomers.

[0029] Preferably, in step (I), the ratio of acrylamide, acrylic acid and acryloxyethyltrimethylammonium chloride is 1 mg: 1 μL: 0.3-0.4 mg; and the amount of fatty alcohol polyoxyethylene ether-9 added is 60-80 wt % of acrylamide.

[0030] Preferably, in step (I), the cross-linking agent comprises N,N-methylenebisacrylamide, and the added molar amount is 1-2% of the total molar mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride.

[0031] Preferably, in step (I), the initiator comprises potassium persulfate or ammonium persulfate, and the amount of the initiator added is 1-3wt% of the total mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride; the catalyst comprises N,N,N',N'-tetramethylethylenediamine, and the amount of the catalyst used is 3-8μL / mL based on the total volume of the hydrogel prepolymer solution.

[0032] Preferably, in step (II), the cross-linking agent includes N,N-methylenebisacrylamide, and the added molar amount is 1-2% of the molar mass of N-isopropylacrylamide; the initiator includes potassium persulfate or ammonium persulfate, and the added amount of the initiator is 1-3wt% of the mass of N-isopropylacrylamide; the catalyst includes N,N,N',N'-tetramethylethylenediamine, and the amount of the catalyst is 3-8μL / mL based on the total volume of the mixed solution.

[0033] Preferably, the mass ratio of N-isopropylacrylamide to cyclodextrin monomer is 1: 10-14. If the cyclodextrin monomer content is too low, the host-guest interaction between cyclodextrin and N-isopropylacrylamide is weak, and the connection strength between the double-layer hydrogel is insufficient; if the cyclodextrin monomer content is too high, it will affect the internal structure and response rate of the hydrogel.

[0034] In the mixed solution of step (II), the concentration of N-isopropylacrylamide is 100-150 mg / mL.

[0035] Preferably, the concentration of N-isopropylacrylamide is 100-130 mg / mL. N-isopropylacrylamide is a decisive monomer for the temperature-sensitive properties of the hydrogel, so its content has a great influence on the response speed of the hydrogel. The hydrogel obtained with a concentration in this range has a fast response speed.

[0036] In step (II), the process of injecting into the mold needs to be completed within 5 minutes, the reaction temperature is ≤30°C, and the reaction time is ≥12 hours.

[0037] Preferably, in step (II), the injection into the mold needs to be completed within 1 minute, the reaction temperature is 0-10°C, and the reaction time is ≥24 hours. N-isopropylacrylamide exhibits better hydrophilicity at low temperatures, and its solubility and polymerization ability in aqueous solution are significantly enhanced.

[0038] In step (III), the process of injecting into the mold needs to be completed within 5 minutes, the reaction temperature is 37-45°C, and the reaction time is ≥15 hours.

[0039] Preferably, in step (III), the injection into the mold needs to be completed within 1 minute, the reaction temperature is 38-40°C, and the reaction time is ≥24 hours. The polymerization process must ensure that the assembled layer hydrogel does not lose too much water due to shrinkage, and that the hydrogel prepolymer solution can be successfully polymerized, so a moderate temperature needs to be selected.

[0040] The present invention also provides a double-layer hydrogel prepared by the preparation method of the double-layer hydrogel. The single-layer hydrogel prepared from the hydrogel prepolymer has a high critical solution temperature characteristic. When the temperature is below 38°C, the hydrogel loses water and shrinks in volume. When the temperature is above 38°C, the hydrogel absorbs water and expands in volume. The assembled layer hydrogel has the opposite low critical solution temperature characteristic. When the temperature is above 33°C, the hydrogel loses water and shrinks in volume. When the temperature is below 33°C, the hydrogel absorbs water and expands in volume. These two opposite temperature response capabilities generate a strong deformation driving force, which improves the response rate of the hydrogel deformation process.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The preparation method of the single-layer hydrogel and the double-layer hydrogel provided by the present invention is simple to operate, has low production cost, and the reaction process is easy to control.

[0043] (2) The single-layer hydrogel prepared by the present invention forms a strong chemical cross-linking network through a chemical cross-linking agent, and also forms a physical cross-linking network through a variety of intermolecular hydrogen bonds, anionic and cationic electrostatic interactions, etc., providing a stress dissipation mechanism and having extremely high strength and toughness. The single-layer hydrogel has controllable transparency, temperature sensitivity, excellent mechanical properties, can achieve rapid and reversible transparency changes, and has a fast response speed.

[0044] (3) The double-layer supramolecular hydrogel obtained by the reversible host-guest interaction between cyclodextrin and N-isopropylacrylamide isopropyl has a tight connection and high connection strength. The double-layer hydrogel has high double-layer bonding strength and can achieve rapid and reversible anisotropic deformation.

[0045] (4) The double-layer hydrogel provided by the present invention has a fast temperature-responsive deformation capability. The single-layer hydrogel has a high critical solution temperature characteristic. When the temperature is below 38°C, the hydrogel loses water and shrinks in volume. When the temperature is above 38°C, the hydrogel absorbs water and expands in volume. The assembled layer hydrogel has an opposite low critical solution temperature characteristic. When the temperature is above 33°C, the hydrogel loses water and shrinks in volume. When the temperature is below 33°C, the hydrogel absorbs water and expands in volume. These two opposite temperature-responsive capabilities generate a strong deformation driving force, which improves the response rate of the double-layer hydrogel deformation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Compression test of the hydrogels prepared in Example 1 and Comparative Examples 1-3: wherein a is the stress-strain curve; b is the morphological change after compression.

[0047] Figure 2 The transparency changes of the hydrogels prepared in Example 1 and Comparative Example 1 at different temperatures, a is Example 1, and b is Comparative Example 1.

[0048] Figure 3 1 is the stress-strain curve of the single-layer hydrogel at different compression rates described in Example 1.

[0049] Figure 4 This is the stretching experiment of the single-layer hydrogel described in Example 1: a is the finger stretching process; b is the length change trend during repeated stretching.

[0050] Figure 5 This is the swelling performance experiment of the single-layer hydrogel described in Example 1: wherein a is the swelling diagram at 50°C; b is the volume change rate at 50°C.

[0051] Figure 6 The water content and equilibrium swelling ratio of the hydrogels prepared in Example 1 and Comparative Examples 1-3 at 25° C. and 50° C. are shown in FIG. 1 , where a is the water content and b is the equilibrium swelling ratio.

[0052] Figure 7 The transparency of the single-layer hydrogel described in Example 1 changes with temperature: a is the swelling diagram at 50°C; b is the UV-visible spectrum at 25°C and 50°C; c is the transmittance change trend during repeated transparency tests; d is the pattern clarity test after the transparency changes.

[0053] Figure 8 Schematic diagram of the dynamic deformation of the double-layer hydrogel described in Example 7: a is the bending process at 50°C; b is the recovery process after bending at 25°C; c is the dynamic curve of bending angle-bending time; d is the change in maximum bending angle during repeated bending. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0055] Examples 1-3

[0056] Acrylamide (200 mg, 2.82 mmol), acrylic acid (200 μL) and β-cyclodextrin monomer (30 mg, 0.025 mmol) were weighed, added to 4 mL of water, stirred and mixed evenly, and transferred to a 50°C water bath for storage; different amounts of acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9, and N,N-methylenebisacrylamide were added respectively; after thorough mixing, argon was introduced for 30 minutes to exhaust oxygen, and the mixture was sealed and allowed to stand for 30 minutes to prevent bubbles from being generated; a certain amount of potassium persulfate was weighed, dissolved in 200 μL of water, added to the mixed solution, and then 20 μL of N,N,N',N'-tetramethylethylenediamine was added to obtain a hydrogel prepolymer solution; the hydrogel prepolymer solution was quickly injected into a mold (60 mm × 60 mm × 1 mm) with a syringe within 1 minute, and reacted at 50°C for 24 hours to obtain the single-layer hydrogel, and the proportions of each raw material are shown in Table 1.

[0057] Comparative Examples 1-3

[0058] The preparation methods of the hydrogels in Comparative Examples 1-3 are the same as those in Example 1, except that the raw materials acryloyloxyethyl trimethyl ammonium chloride and / or fatty alcohol polyoxyethylene ether-9 are not added, and different amounts of crosslinking agents and initiators are used. The proportions of the raw materials are shown in Table 1.

[0059] Table 1 Ratios of raw materials in Examples 1-3 and Comparative Examples 1-3

[0060]

[0061] Embodiment 4-6

[0062] The preparation method of the hydrogel in Examples 4-6 is the same as that in Examples 1-3, except that the raw material cyclodextrin monomer is α-cyclodextrin monomer.

[0063] Examples 7-9 and Comparative Examples 4-6

[0064] (1) First, the hydrogel prepolymer solutions in Examples 7-9 and Comparative Examples 4-6 were prepared according to the raw material ratios and methods in Examples 1-3 and Comparative Examples 1-3;

[0065] (2) Weigh N-isopropylacrylamide and N,N-methylenebisacrylamide at the same time, add them to 3 mL of water, stir and mix evenly, move to a 0-5°C ice water bath, pass argon for 30 minutes to exhaust all oxygen, seal and let stand for 30 minutes to prevent bubbles; weigh a certain amount of potassium persulfate, dissolve it in 200 μL of water, add it to the mixed solution, and then add 20 μL of N,N,N',N'-tetramethylethylenediamine to obtain a mixed solution of the assembly layer hydrogel; quickly inject it into a mold (60 mm×60 mm×1 mm) with a syringe within 1 minute, react at 0-5°C for 24 hours to obtain the assembly layer hydrogel.

[0066] (3) The mold in step (2) was replaced with a 60 mm × 60 mm × 2 mm mold, and the single-layer hydrogel prepolymer solution in step (1) was rapidly injected within 1 min, and reacted at 40° C. for 24 h to obtain the double-layer hydrogel. The raw material ratios in Examples 7-9 and Comparative Examples 4-6 are shown in Table 2.

[0067] Table 2 Ratios of raw materials in Examples 7-9 and Comparative Examples 4-6

[0068]

[0069] Examples 10-12

[0070] The preparation method of the double-layer hydrogel in Examples 10-12 is the same as that in Examples 7-9, the only difference is that the raw material cyclodextrin monomer in the hydrogel prepolymer solution of the single-layer hydrogel is α-cyclodextrin monomer.

[0071] Performance Testing

[0072] The polyacrylamide-acrylic acid hydrogel system was selected by the change of mechanical properties and transparency. The mechanical properties of the hydrogels prepared in Example 1 and Comparative Examples 1-3 were tested, and the results were as follows: Figure 1 To prevent the sample from sliding on the experimental table, the hydrogel sample for compression testing is in the shape of a cylinder. Figure 1 It can be found from a in that Example 1 containing both acryloyloxyethyl trimethyl ammonium chloride and fatty alcohol polyoxyethylene ether-9 has the best mechanical properties, with a maximum deformation of 98.7% and a maximum stress of 740 kPa. The mechanical properties of other hydrogels are poor, such as the hydrogel in Comparative Example 3, which has the weakest deformation ability. This is because its cross-linking density is the lowest, the degree of freedom of the polymer chain is high, and the interaction between the polymer chains is weakened, resulting in the worst compression performance. In addition, from Figure 1 As can be seen from b, Example 1 can still maintain its initial state after multiple compression cycles, while Comparative Examples 1-3 all suffered varying degrees of damage, cracks or even ruptures, and could not meet ideal application conditions.

[0073] The results of the transparency changes of the hydrogels prepared in Example 1 and Comparative Example 1 are as follows: Figure 2 As shown in a, the transparency of the hydrogel in Example 1 is significantly different at high and low temperatures. It is completely opaque at 25°C and becomes completely transparent at 50°C. However, the transparency of the hydrogels in Comparative Examples 1-3 does not change significantly. Representative pictures are shown in Figure 2 As shown in b in (Comparative Example 1).

[0074] The hydrogel obtained in the preferred embodiment 1 was further tested for its performance.

[0075] (1) Mechanical properties test

[0076] like Figure 3 As shown in the stress-strain curves of the hydrogel at different compression rates in Test Example 1, when the compression rates are set to 5, 10, 15, and 20 mm / min, respectively, the maximum stress of the hydrogel is the same, and although the maximum deformation is slightly reduced, it is maintained above 90%, mainly because the interval time for this series of tests using the same hydrogel is short, and the state of the hydrogel after rebound is slightly limited. This shows that the compression performance of the hydrogel is excellent and has great application advantages.

[0077] like Figure 4 As shown in a, the stretching efficiency of the hydrogel of Example 1 was tested by manual stretching. The hydrogel was stretched from the original 1.5 cm to about 9 cm without breaking, and it was able to return to its original state after being released, and its length and width did not change. Calculations show that the elongation can reach at least 500%, which is much greater than that of traditional thermosensitive hydrogels. Figure 4 As shown in b, the stretching test of the hydrogel was repeated more than 10 times, and the tensile properties remained stable. The test process was carried out at room temperature, indicating that the physical cross-linking effect in the hydrogel was strong at this time, and the polymer chains stretched without breaking when stretched.

[0078] (2) Temperature response performance test

[0079] like Figure 5 As shown in a, a single-layer hydrogel of Example 1 with a diameter of 9.5 mm is immersed in a 50°C water bath, and the volume change trend is observed and recorded by coordinate paper. It can be seen that after 5 seconds, the hydrogel shows obvious volume change and transparency change. After 10 seconds, the volume of the hydrogel reaches about 13 mm, and it changes from opaque to completely transparent, indicating that the hydrogel system has a fast temperature response performance. Figure 5 b quantitatively measured the volume change rate of the hydrogel in Example 1 over time. At 11 seconds, the swollen volume had reached about 256% of the original volume, that is, the volume increase rate was 156%. After immersion for 15 seconds, the volume increase rate of the hydrogel reached more than 162% and no longer changed significantly. The above data show that the volume of Example 1 changed significantly after absorbing water, and the expansion process was very rapid.

[0080] Figure 6 The water content and equilibrium swelling ratio of Example 1 and Comparative Examples 1-3 were compared. From the test results, it can be seen that the water content of the hydrogel of Example 1 is 95.4% at 50°C, and the water content at 25°C is reduced to 67.7%, which is a significant change, while the water content of Comparative Examples 1-3 changes by only 1-2% ( Figure 6Similarly, the equilibrium swelling ratio values ​​of Example 1 at 25°C and 50°C vary greatly, increasing from 2 to 21.1, while the equilibrium swelling ratios of Comparative Examples 1-3 have a much smaller variation trend ( Figure 6 b) in the above.

[0081] (3) Transparency change test

[0082] Figure 7 a. The hydrogel of Example 1 in swelling equilibrium at room temperature is placed in a watch glass, and 50°C water is injected with a syringe. Its transparency increases instantly and begins to change to a transparent state. After 10 seconds, it becomes completely transparent. After cooling to 25°C for 5 seconds, it changes to an opaque state.

[0083] The transmittance (400nm-700nm) of Example 1 at 25°C and 50°C was tested by UV-Vis spectroscopy. The results are as follows: Figure 7 As shown in b, at 25°C, the transmittance of the hydrogel remains in the range of 0-2%, which can be considered completely opaque, while at 50°C, the transmittance of the hydrogel is above 97%, that is, it remains completely transparent. In addition, the transmittance at 25°C and 50°C during the 10 repetitions was measured. Figure 7 As can be seen from c in the figure, in multiple tests, the transmittance of Example 1 remained consistent with the result of the first test, indicating that the reversible change of its transparency was not negatively affected and lossless application could be achieved.

[0084] Figure 7 d in FIG. 1 shows that when the “Seeking Truth Eagle” pattern is placed under Example 1 and the temperature is raised to 50° C., the pattern outline gradually becomes clear, and this process is reversible.

[0085] (4) Reversible deformation performance test

[0086] The characteristics of the single-layer hydrogel prepared in Example 1 are low-temperature water loss shrinkage and high-temperature water absorption expansion, and the characteristics of the assembled layer hydrogel are high-temperature hydrophobic shrinkage and low-temperature hydrophilic swelling. Two temperature response systems with opposite trends are integrated into the same hydrogel, and the dynamic reversible deformation behavior of the hydrogel is realized by assembling a double-layer structure. The double-layer hydrogel is firmly connected through the host-guest interaction between cyclodextrin (the single-layer hydrogel) and N-isopropylacrylamide isopropyl (assembly layer hydrogel). The opposite thermal response capabilities of the two produce a strong deformation driving force, which improves the response rate of the bending process.

[0087] like Figure 8 As shown in a and b in the figure, the bending deformation of the double-layer hydrogel in a 50°C water bath and the recovery process in a 25°C water bath can be clearly observed with the naked eye. The process of the hydrogel from a straight line to a semicircle and then to a complete circle only takes 30 seconds, and the recovery time is about 3 minutes.

[0088] Figure 8 Figure c shows the quantitative analysis curve of the angle change and deformation rate during the deformation process. The center angle of the circle where the double-layer hydrogel is located is the bending angle. The determination of the bending direction can refer to the settings in the figure. It can be clearly seen from the figure that the center angle increases rapidly from 180° to 316° within 30s during the bending process, and then returns to the original 180° within the next 150s. The bending-recovery process was repeated more than 10 times. As shown in d in 8, the bending angle switches between 180° and 316°, indicating that the deformation process has good repeatability. And after repeated tests, the double-layer hydrogel is still firmly bonded together, verifying the connection strength between the single-layer hydrogel and the assembly layer hydrogel, reflecting the stability of the host-guest interaction between isopropyl and cyclodextrin. The prepared double-layer hydrogel system can meet the strength requirements of anisotropic deformation hydrogel actuators, and has a fast response rate and excellent mechanical properties.

[0089] The above-described embodiments provide a detailed description of the technical solutions of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a single-layer hydrogel, characterized in that: The following steps are involved: (1) dissolving acrylamide, acrylic acid and cyclodextrin monomers in water, adding acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9 and a crosslinking agent and mixing thoroughly; then adding an initiator and a catalyst to obtain a hydrogel prepolymer solution; (2) injecting the hydrogel prepolymer solution in step (1) into a mold to react and obtain a single-layer hydrogel; In step (1), the ratio of acrylamide, acrylic acid, and acryloxyethyl trimethyl ammonium chloride is 1 mg: 1 µL: 0.3-0.4 mg; and the amount of fatty alcohol polyoxyethylene ether-9 added is 60-80 wt % of acrylamide.

2. A method for preparing a double-layer hydrogel, characterized in that: The following steps are involved: (I) dissolving acrylamide, acrylic acid and cyclodextrin monomers in water, adding acryloyloxyethyl trimethyl ammonium chloride, fatty alcohol polyoxyethylene ether-9 and a crosslinking agent and mixing them thoroughly; then adding an initiator and a catalyst to obtain a hydrogel prepolymer solution; (II) N - isopropyl acrylamide and a cross-linking agent are dissolved in deionized water and mixed evenly, an initiator and a catalyst are added to obtain a mixed solution, and the mixed solution is injected into a mold for reaction to obtain an assembly layer hydrogel; (III) injecting the hydrogel prepolymer solution of step (I) into the mold of step (II) to react and obtain the double-layer hydrogel; In step (I), the ratio of acrylamide, acrylic acid, and acryloyloxyethyl trimethyl ammonium chloride is 1 mg: 1 µL: 0.3-0.4 mg; the amount of fatty alcohol polyoxyethylene ether-9 added is 60-80 wt% of acrylamide; N -The mass ratio of isopropyl acrylamide to cyclodextrin monomer is 1:10-14.

3. The method according to claim 1 or 2, characterized in that: In step (1) and step (I), the molar amount of the crosslinking agent added is 1-2% of the total molar mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyl trimethyl ammonium chloride; the amount of the initiator added is 1-3 wt% of the total mass of the three raw materials of acrylamide, acrylic acid and acryloyloxyethyl trimethyl ammonium chloride; and the amount of the catalyst used is 3-8 μL / mL based on the total volume of the hydrogel prepolymer solution.

4. The method according to claim 1, characterized in that In step (2), the injection process into the mold needs to be completed within 5 minutes, and the reaction temperature should be ≥50 o C, reaction time ≥16 h.

5. A single-layer hydrogel prepared according to the method of claim 1.

6. The method according to claim 2, characterized in that: The mixed solution N -The concentration of isopropylacrylamide is 100-150 mg / mL.

7. The method according to claim 2, characterized in that: In step (II), the added molar amount of the cross-linking agent is N -1-2% of the molar mass of isopropyl acrylamide; the amount of the initiator added is N -1-3wt% of the mass of isopropyl acrylamide; Based on the total volume of the mixed solution, the amount of the catalyst used is 3-8 μL / mL.

8. The method according to claim 2, characterized in that: In step (II), the injection process into the mold needs to be completed within 5 min, and the reaction temperature is ≤30 o C, reaction time ≥12 h.

9. The method according to claim 2, characterized in that: In step (III), the process of injecting into the mold needs to be completed within 5 minutes, the reaction temperature is 37-45°C, and the reaction time is ≥15 hours.

10. A double-layer hydrogel prepared according to the method of claim 2.